Konsekuensi Sistem Proporsional Terbuka terhadap Kesadaran Hukum - Achmad Hafy Akmal Moeslim; Boy Dawud Mochamad Fadillah (Universitas Islam Balitar, 2025)
The electoral system is a crucial aspect in supporting the existence of democracy in Indonesia. Currently, Indonesia employs an open proportional system in conducting elections. The researcher utilizes a literature study approach to analyze the open proportional system. This electoral system has both positive and negative implications for societal phenomena. On the positive side, it promotes greater transparency among legislative candidates, allowing the public to scrutinize the track records of the candidates they choose. However, on the negative side, it leads to issues such as widespread money politics, high political costs, and the emergence of politicians who prioritize popularity over competence and credibility. Therefore, this journal examines whether the open proportional system is an effective electoral system. The researcher also analyzes its implications for public legal awareness and the participation of society in elections organized by the state.